Evaluasi Program Blended Learning terhadap Hasil belajar Siswa - Nur Hidayat (Peneliti.net, 2021)
The goal of this study is to give an overview of blended learning's application, particularly when it comes to distance learning (PJJ), limited PTM, and blended learning's application due to the covid-19 pandemic. This research takes a qualitative approach and employs the case study method. Interviews, observation, and documentation studies are used to collect data. Based on the findings of the study, the teacher creates lesson plans, syllabi, limited face-to-face scheduling, teaching materials, and evaluation tools in the form of soft files during the planning process. The learning process is divided into three stages: preliminary, core, and concluding activities. Giving assignments, both written and practical, as well as UAS, are used to assess learning. There were a number of challenges faced by both students and teachers at the time of implementation